Serum apelin and resistin levels in patients with impaired fasting glucose, impaired glucose tolerance, type 2 diabetes, and metabolic syndrome - Onalan, Erhan; Yakar, Burkay; Barim, Abdullah Onder; Gursu, Mehmet Ferit (Via Medica, 2020)
Introduction: The aim of this study was to investigate serum apelin and resistin levels in patients with impaired fasting glucose, impaired glucose tolerance, type 2 diabetes and metabolic syndrome. Material and methods: The study comprised 18 patients with type 2 diabetes mellitus (T2DM) (nine females, nine males), 18 patients with impaired fasting glucose (IFG) (nine females, nine males), 18 patients with impaired glucose tolerance (IGT) (nine females, nine males), 18 patients with metabolic syndrome (MeS) (nine females, nine males), and 16 healthy individuals (eight females, eight males); serum adiponectin, apelin, resistin levels, fasting and postprandial blood glucose, insulin resistance markers, and lipid parameters were measured. Results: In the study, serum apelin levels were determined to be significantly lower in IGT, MeS, and T2DM groups compared with the control group (p = 0.002, p = 0.006, and p < 0.001, respectively). Serum resistin levels were determined to be significantly higher in IGT and T2DM groups compared with the control group (p < 0.001 and p < 0.001, respectively). Conclusions: Apelin and resistin are thought to affect glucose metabolism and insulin resistance. Apelin is an important indicator in individuals with IGT in the prediabetic period and may play a role in preventing diabetic complications and treatment of T2DM.
Keywords: metabolic syndrome; pre-diabetes; apelin; resistin